1998
DOI: 10.1200/jco.1998.16.2.567
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity in pleural effusions: diagnostic significance.

Abstract: Our results indicate that the detection of telomerase activity may be a useful adjunct to cytopathologic methods in the diagnosis of malignant pleural effusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 29 publications
3
33
1
1
Order By: Relevance
“…Likewise, the rate of positive telomerase activity in nonmalignant cytological samples has been reported to be y10% in previous reports [9,17,21]. Among the 46 benign samples, a total of nine (19.6%) samples, composed of six with empyema and three with tuberculosis effusions, showed telomerase expression in the present study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Likewise, the rate of positive telomerase activity in nonmalignant cytological samples has been reported to be y10% in previous reports [9,17,21]. Among the 46 benign samples, a total of nine (19.6%) samples, composed of six with empyema and three with tuberculosis effusions, showed telomerase expression in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, telomerase expression has been shown to be a potential diagnostic biomarker in the fluids of body cavities, however, the present authors are aware of only a few reports investigating the telomerase activity with special reference to pleural effusions [6,17]. These reports showed that the sensitivity of telomerase activity in malignant pleural effusions were 67 and 91%, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…47 In bronchial washing cell samples including bronchio-alveolar lavage (BAL) samples, the sensitivity of telomerase is as high as 80% of that in primary cancer tissues resected. [48][49][50] In addition, Yang et al 51 showed more convincing evidence for the clinical utility of telomerase in pleural effusions in three groups: (a) malignant pleural effusions as diagnosed by cytology; (b) nonmalignant pleural effusions; and (c) pleural effusions that were suspected to be malignant, but the findings were inconclusive by cytology. Of 144 samples, telomerase activity was detected in 91% (64 of 70) of malignant samples, 91% (20 of 22) of suspicious samples and only 5.8% (three of 52) of nonmalignant samples.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the view that, as is the case with exsudates, cytologic and molecular evaluation is warranted in transudates as well. (Yang et al, 1998;Chang et al, 2002;Grünewald et al, 2002). The big advantage of FISH is the direct visualisation of tumour cells exhibiting numeric chromosomal aberrations (Figure 1).…”
Section: Discussionmentioning
confidence: 99%